Improvement in Knee Loading After Use of Specialized Footwear for Knee Osteoarthritis: Results of a Six‐Month Pilot Investigation. Issue 5 (23rd April 2013) - Shakoor, Najia; Lidtke, Roy H.; Wimmer, Markus A.; Mikolaitis, Rachel A.; Foucher, Kharma C.; Thorp, Laura E.; Fogg, Louis F.; Block, Joel A.
Abstract Objective Biomechanical interventions for knee osteoarthritis (OA) aim to improve pain and retard disease progression by decreasing knee loading. This study was undertaken to evaluate the effects of 6 months of use of flat, flexible footwear (the mobility shoe) on knee loading in OA. Methods Subjects with knee OA underwent baseline gait analyses under conditions of walking in their own shoes, walking in mobility shoes, and walking barefoot. Thereafter, subjects wore the mobility shoes at least 6 hours per day for 6 days per week. Gait evaluations were repeated at 6, 12, and 24 weeks. An intent‐to‐treat analysis was performed to assess the longitudinal effects on knee loading with the shoe intervention. Results Compared to knee loading at baseline with the participants' own shoes, there was an 18% reduction in the knee adduction moment (KAM) by 24 weeks with the mobility shoes (P < 0.001) and no significant differences in the KAM by 24 weeks between mobility shoe and barefoot walking (P = 0.192). Over the 6 months of followup, participants also experienced an 11% reduction in the KAM when walking in their own shoes (P = 0.002) and a 10% reduction in the KAM when walking barefoot (P = 0.002 for the whole followup), as compared to these values at baseline under the same conditions. Conclusion This study suggests that use of flat, flexible footwear results in significant reductions in knee loading in subjects with OA. By 24 weeks, there is evidence of a gait adaptation with sustained load reduction even when the mobility shoes are removed, suggesting that footwear may serve as a biomechanical training device to achieve beneficial alterations in gait mechanics for knee OA.